Technology Usage and Online Sales: An Empirical Study - De, Prabuddha; Hu, Yu (Jeffrey); Rahman, Mohammad S. (Management Science, 2010)
Despite the widespread adoption of search and recommendation technologies on the Internet, empirical research that examines the effect of these technologies is scarce. How do online consumers use these technologies? Does consumers' technology usage have an effect on the sales to them or their purchasing patterns? This paper empirically measures consumers' usage of website technologies by analyzing server log data. We match technology usage data to sales data, controlling for consumers' historical purchasing behavior. Our unique data set allows us to reveal the relationship between technology usage and online sales. Our analyses show that consumers' information technology usage has a significant effect on the sales to them, but this effect varies for different technologies and across different products. In particular, the use of directed search has a positive effect on the sales of promoted products, whereas it has a negative effect on the sales of nonpromoted products. In contrast, the use of a recommendation system has a positive effect on the sales of both promoted and nonpromoted products. Surprisingly, the use of nondirected search has an insignificant effect on online sales.